AUTHOR’S EXPERIENCE IN TRAINING PUPILS OF SPECIALIZED OUTOF-SCHOOL EDUCATIONAL INSTITUTIONS TO RESEARCH WORK BY MEANS OF INFORMATIONAL AND COMMUNICATION TECHNOLOGIES - Voronkin, O. (Journal of Information Technologies in Education (ITE), 2016)
In the article the author’s experience in pupils’ training of Junior Academy of Sciences of Ukraine to research work by means of informational and communication technologies is presented.The three-tiered approach (popular science, experimental, fundamental levels) to the organization of personal oriented study in Physics covered such didactic principles as accessibility, visibility,scientific and systematic is considered. At the first level, pupils should be inculcated by interest in physics, its specificity, the terms etc. At the second level the experiment and demonstration of physical phenomena have a paramount importance, which aims to encourage students to make selffacilitated conclusions. At the third level the laboratory works and method of problem learning allow students to develop the ability independently to solve physical tasks. It is concluded that at each of these levels the means of information and communication technologies should be used. As an example, the author reviews the experience of open online course «Introduction to Physics of Sound», designed for pupils of specialized out-of-school educational institutions. We presented the main issues of the online course and examples of cognitive activity of pupils.